2007
DOI: 10.1258/000456307780945633
|View full text |Cite
|
Sign up to set email alerts
|

Within-subject biological variation in disease: collated data and clinical consequences

Abstract: Quantitative data on the components of biological variation (BV) are used for several purposes, including calculating the reference change value (RCV) required for the assessment of the significance of changes in serial results in an individual. Pathology may modify the set point in diseased patients and, more importantly, the variation around that set-point. Our aim was to collate all published BV data in situations other than health. We report the within-subject coefficient of variation (CV(I)) for 66 quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
2
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 32 publications
2
113
2
9
Order By: Relevance
“…Normal biological variability comprises within‐subject (intraindividual) and among‐subject (interindividual) variation, both of which might be similar or different between health and various disease states 18, 24…”
Section: Biomarker Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal biological variability comprises within‐subject (intraindividual) and among‐subject (interindividual) variation, both of which might be similar or different between health and various disease states 18, 24…”
Section: Biomarker Characteristicsmentioning
confidence: 99%
“…Sources of biological variation include rhythmic expression or secretion, variation in gastrointestinal passage or patchy distribution of cells expressing and releasing a biomarker measured in feces, and the metabolism and half‐life of a biomarker (determined by its size, charge, hydrophobicity, and route of excretion) 18, 24. Such sources of biological variation must be recognized and strategies developed to counterbalance such variation (eg, by collecting specimens on multiple days or at a certain time of the day).…”
Section: Biomarker Characteristicsmentioning
confidence: 99%
“…In consequence, the real RCV in these patients would be higher than in the healthy. However, a compilation of known data on CV I in diseases [24] and comparison with relevant data in the healthy suggests that, in general, CV I are indeed similar in health and chronic stable disease. In conclusion, for most quantities, data on health can be used appropriately in monitoring of disease [25].…”
Section: Limits Of the Studymentioning
confidence: 99%
“…Between-subjects or inter-individual biological variation is defined as the difference between the set-points of individuals (13,14). Quantitative data of the components of biological variation have been used to assess the utility of population-based reference intervals through the index of individuality (II) (15,16), and to calculate the reference change value (RCV) required for the assessment of the significance of changes in serial results from an individual (17,18). Likewise, it has been suggested that desirable analytical quality specifications are best based on components of biological variation (19,20).…”
Section: Introductionmentioning
confidence: 99%